Surface-Runoff Characteristics under Simulated Rainfall Conditions (Progressive Agriculture, 2014)
This paper describes a rainfall-runoff simulation study, conducted in a laboratory to investigate surface runoff characteristics, verify unit hydrograph assumption and investigate the nature of the recession constant. A hydrology bench consisting of a metallic tray with an over head sprinkler system was used for this study. The metallic tray with soil bed and a river network acted as a small catchment. The over head sprinkler system consisting of spray nozzles acted as rainfall simulator. Different rainfall intensities and durations were taken as the treatments for the experiments. Surface runoff volume was collected at 10 secondly pulses of time in each experiment. Collected data were then processed and analyzed to explain the results. Unit hydrographs were developed from the surface runoff hydrographs for different rainfall durations and intensities. Recession constant K was calculated from the recession limb of each surface runoff hydrograph by optimization. Investigations show that runoff volume, runoff generation rate and peak runoff rate increase with the increasing rainfall duration. However, the peak runoff rate per sec of effective rainfall decreases with the increasing rainfall duration. There is also an evidence of the effects of rainfall intensity on runoff characteristics but no specific trend is identified. This study also reveals that the assumption of linearity between runoff volume and hydrograph ordinates is partially valid with some error which may be attributed to the non-uniform distributions of rainfall. Nature of recession constant suggests that the recession hydrograph is not only a function of catchment characteristics but also depends on rainfall intensities.DOI: http://dx.doi.org/10.3329/pa.v24i1-2.19175 Progress. Agric. 24(1&2): 219 - 227, 2013